2014
DOI: 10.1111/febs.12807
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid aggregation and deposition of human islet amyloid polypeptide at membrane interfaces

Abstract: Amyloid deposition of human islet amyloid polypeptide (hIAPP) within the islets of Langerhans is a pathological feature of type 2 diabetes mellitus. Substantial evidence indicates that the membrane-mediated aggregation and subsequent deposition of hIAPP are linked to dysfunction and death of pancreatic b-cells, but the molecular processes of hIAPP deposition are poorly understood. In this study, we examined the membranemediated aggregation and deposition of hIAPP at supported planar lipid bilayers with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
(155 reference statements)
0
19
0
1
Order By: Relevance
“…Previous theoretical and experimental studies from our laboratory and others (12)(13)(14) have demonstrated that the tendency of a dilute protein to form fibrils is significantly enhanced in solutions containing high concentrations of nominally inert polymers and proteins, a phenomenon that is attributed primarily to excluded volume or macromolecular crowding (15)(16)(17). Other theoretical and experimental studies from our laboratory and others (18)(19)(20) have demonstrated that the presence of adsorbing surfaces can significantly enhance the tendency of dilute proteins to form adsorbed linear and nonlinear aggregates. For these reasons, we speculated that the presence of both high concentrations of inert macromolecules and surfaces to which the fiber-forming protein can adsorb might have a cumulative effect on fiber formation by the dilute protein that is greater than the sum of the separate effects of crowding and adsorption.…”
Section: Introductionmentioning
confidence: 91%
“…Previous theoretical and experimental studies from our laboratory and others (12)(13)(14) have demonstrated that the tendency of a dilute protein to form fibrils is significantly enhanced in solutions containing high concentrations of nominally inert polymers and proteins, a phenomenon that is attributed primarily to excluded volume or macromolecular crowding (15)(16)(17). Other theoretical and experimental studies from our laboratory and others (18)(19)(20) have demonstrated that the presence of adsorbing surfaces can significantly enhance the tendency of dilute proteins to form adsorbed linear and nonlinear aggregates. For these reasons, we speculated that the presence of both high concentrations of inert macromolecules and surfaces to which the fiber-forming protein can adsorb might have a cumulative effect on fiber formation by the dilute protein that is greater than the sum of the separate effects of crowding and adsorption.…”
Section: Introductionmentioning
confidence: 91%
“…Aberrant aggregation of proteins into amyloid deposits is a hallmark of many human pathologies, for example, Alzheimer's disease, Parkinson's disease, and type 2 diabetes . Amyloid deposits contain amyloid fibrils characterized by cross‐β structure consisting of stacked β‐sheets held together by interpeptide hydrogen bonding along the long fibrillar axis .…”
Section: Introductionmentioning
confidence: 99%
“…From a molecular point of view, obesity leads to calcium dyshomeostasis ( 30 ), increased concentration of free fatty acids (FFA) ( 42 ), and cholesterol ( 43 , 44 ). All of these effects have been shown to be involved in the molecular mechanisms leading to hIAPP-induced disruption of Langerhans’ β-cells ( 11 , 25 , 45 , 46 ). Thus, these metabolic effects could all represent a common link between environmental factors and molecular mechanisms.…”
Section: Weight Gain and T2dm: The Role Of Free Fatty Acidsmentioning
confidence: 99%